Adjustment elusiveness: An empirical investigation of the effects of cross-cultural adjustment on general assignment satisfaction and withdrawal intentions - Luisa Helena Pinto (2012)
The research reported here explores the relationship between cross-cultural adjustment and general satisfaction with the assignment and withdrawal intentions. Responses from an international sample of 166 expatriates, currently assigned to 39 different countries, indicate that perceived cross-cultural adjustment does not predict expatriates' general assignment satisfaction, though satisfaction predicts withdrawal intentions. Work adjustment predicts assignment withdrawal intentions, but does not predict the other two withdrawal dimensions: withdraw from the organization and the occupation. Implications of the findings for theory and practice, along with suggestions for future research, are discussed.